The Influence Of Electronic Word Of Mouth (E-Wom), Brand Image, And Service Quality On Customer Loyalty Through Customer Satisfaction In Maxim Online Transportation Services In Jabodetabek - Asikin, Munawar; Fikri, Muhammad Jafar (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
This study aims to analyze the influence of electronic word of mouth (E-WOM), brand image, and service quality on customer loyalty, with customer satisfaction as an intervening variable in the context of the Maxim online transportation service. The research method employed is a quantitative approach using Structural Equation Modeling (SEM) analysis with the JASP application version 0.19.3. The research sample was obtained using purposive sampling, involving 100 respondents who are users of Maxim services in the Greater Jakarta area (Jabodetabek). Data were collected through questionnaires distributed both online and offline, with criteria that respondents must have used Maxim's services more than twice in the last three months and be over 18 years old. The results of the study show that E-WOM does not have a significant effect on customer satisfaction or loyalty, either directly or through customer satisfaction as a mediating variable. In contrast, brand image and service quality have a positive and significant effect on customer satisfaction. Additionally, customer satisfaction has been proven to have a positive and significant impact on customer loyalty and mediates the relationship between brand image and service quality with customer loyalty. However, service quality does not have a direct significant effect on customer loyalty, indicating that customers tend to be more loyal due to their satisfaction level rather than service quality alone. These findings suggest that to improve customer loyalty, Maxim needs to focus on enhancing brand image and service quality, as well as strengthening strategies to increase customer satisfaction. Although E-WOM is often regarded as an important factor in digital marketing, it does not directly contribute to customer loyalty in the context of online transportation services.